Mexican Pink: Color Identity fop A Nation - Mukhopadhyay, T. P.; Gurieva, N.; Fernanda, P. L. M. (ХНУРЭ, 2016)
Mexican people are renown ed all over the world for their spontaneousness and charismatic culture, which also give them their charming and vivacious identity as individuals: the color rosa Mexicano or Mexican Pink forms a part of that cultural identity. We are investigating the origin of this color and would like to prove that the term indeed represents a color that has long been embedded in indigenous traditions and later Mestizo manifests, although it appears that this color did not have a name in Spanish before the last century.
Keywords: mexican charismatic culture; Mexican Pink forms